A View of Islamic Family Law on the Neglect of Children’s Growth and Development Rights by Parents (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
Parents are the first education obtained by children. All education received by children begins with the closest family education, whom are the child’s parents. Proper parenting that fosters children’s affection and attention can manage children’s emotions when socializing among society. The method used in this article is qualitative method, which is a method of producing descriptive data. This research also uses maqasid sharia theory and hadhanah with descriptive methods. Researchers used data collection including: observation, interviews, and documentation. Researchers participated directly in the observation. The research was conducted in 2022 by looking at four cases involving children. Based on the field findings, the conclusions of this research are: 1) Factors that influence the neglect of children’s growth and development rights are parents’ income, parents’ education, and the number of children. 2) Handling of cases involving children by litigation and non-litigation. Litigation is taking the judicial route, and non-litigation is by taking the deliberation method to make peace with the agreement between the two parties to the conflict. 3) The view of Islamic family law is in accordance with the theory of maqashid al-syari’ah and hadhanah.